2012
DOI: 10.1186/1748-717x-7-25
|View full text |Cite
|
Sign up to set email alerts
|

Post-radiation increase in VEGF enhances glioma cell motility in vitro

Abstract: BackgroundGlioblastoma multiforme (GBM) is among the most lethal of all human tumors, with frequent local recurrences after radiation therapy (RT). The mechanism accounting for such a recurrence pattern is unclear. It has classically been attributed to local recurrence of treatment-resistant cells. However, accumulating evidence suggests that additional mechanisms exist that involve the migration of tumor or tumor stem cells from other brain regions to tumor bed. VEGFs are well-known mitogens and can be up-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 32 publications
6
67
0
Order By: Relevance
“…[108] However, single agents targeting the PAM pathway have been reported to be an inefficient approach in MB and to increase invasion in the surviving fraction of GBM. [109] Therefore, new therapeutic approaches should be based on increasing the therapeutic window by targeting two different routes, namely the PAM and ERK pathways, or on combining PAM inhibitors with chemotherapeutic agents. [110] MicroRNAs have also been shown to play an important role in various CNS malignancies, and miR-142-5p and miR-25 are upregulated in all of them.…”
Section: Emt Cell Invasion and Motilitymentioning
confidence: 99%
“…[108] However, single agents targeting the PAM pathway have been reported to be an inefficient approach in MB and to increase invasion in the surviving fraction of GBM. [109] Therefore, new therapeutic approaches should be based on increasing the therapeutic window by targeting two different routes, namely the PAM and ERK pathways, or on combining PAM inhibitors with chemotherapeutic agents. [110] MicroRNAs have also been shown to play an important role in various CNS malignancies, and miR-142-5p and miR-25 are upregulated in all of them.…”
Section: Emt Cell Invasion and Motilitymentioning
confidence: 99%
“…8,9 In addition, glioma cell mobility was enhanced by adding irradiated-conditioned medium to nonirradiated cells. 3 We hypothesize that the enhanced invasive ability of irradiated glioma cells is mediated both directly via glioma cells themselves and indirectly via the increased expression of various mediators.…”
Section: Discussionmentioning
confidence: 99%
“…3,14 Clinical studies of patients with rectal cancer found that monotherapy with the anti-VEGF antibody bevacizumab upregulates SDF-1a and CXCR4 expression in tumour cells, and higher SDF-1a plasma levels during bevacizumab treatment were significantly associated with distant metastasis. 15 Simultaneous inhibition of both VEGF and SDF-1a/CXCR4 might enhance the efficacy of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF is critical for not only angiogenesis but also prostate-cancer-mediated osteoblastic activity (93). IR modulates VEGF expression through multiple mitogen activated protein kinases (MAPK)-dependent pathways (137) and enhances glioma cell motility through vascular endothelial growth factor receptor 2 (VEGFR2) signaling pathways (87). Since prostate cancer cells lack expression of specific VEGF receptors, especially VEGFR2, IR-induced VEGFs are more likely to promote prostate cancer progression indirectly through their functions in stromal cells, in particular, endothelial cell survival, and as a chemotactic agent within the tumor microenvironment (93).…”
Section: Role Of Ros In the Interaction Between Stroma And Prostate Cmentioning
confidence: 99%